2005
DOI: 10.14411/eje.2005.022
|View full text |Cite
|
Sign up to set email alerts
|

Digestive proteolytic activity in the gut and salivary glands of the predatory bug Podisus maculiventris (Heteroptera: Pentatomidae); effect of proteinase inhibitors

Abstract: Abstract. Proteinase activity in the midgut of the pentatomid stinkbug Podisus maculiventris was investigated. The optimal pH for adult and nymph proteolysis was pH 6.0 and pH 6.5, respectively. Proteinase activity was characterised using a range of diagnostic inhibitors. Activity of both adult and nymphal gut extracts, detected by the hydrolysis of Z-Phe-Arg-pNA, was inhibited to <20% of control levels by several inhibitors (e.g. E-64 and chicken egg white cystatin) associated with the inhibition of cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 43 publications
(35 reference statements)
5
40
0
Order By: Relevance
“…Our results, however, revealed that the collagenase extracted from the salivary glands of P. maculiventris is sensitive to EDTA and so collagenase is a metalloproteinase. In line with our findings, Bell et al (2005) showed that the salivary gland extract of P. maculiventris is affected by EDTA, implying that there is a presence of metalloproteinase in the salivary glands. A recent study on the closely related species P. nigrispinus, definitely revealed that collagenase is a metalloproteinase enzyme and it is one of the most important proteases in the salivary gland and midgut of the predatory bug (Fialho et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results, however, revealed that the collagenase extracted from the salivary glands of P. maculiventris is sensitive to EDTA and so collagenase is a metalloproteinase. In line with our findings, Bell et al (2005) showed that the salivary gland extract of P. maculiventris is affected by EDTA, implying that there is a presence of metalloproteinase in the salivary glands. A recent study on the closely related species P. nigrispinus, definitely revealed that collagenase is a metalloproteinase enzyme and it is one of the most important proteases in the salivary gland and midgut of the predatory bug (Fialho et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The salivary glands' collagenase clearly is a major factor in the extra-oral digestion process and liquefaction of the internal host body's organs. Collagenase alongside serine proteases (Bell et al 2005) are the main enzymes present in the salivary glands of the P. maculiventris. Optimal pH of total proteolytic activity of the salivary glands is associated with optimum pH of collagenase and serine proteases activity in the P. maculiventris (Bell et al 2005) and other asopin species (Cohen 1995;Oliveira et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations